Augustine and postmodernism : confessions and circumfession - Caputo, John D.; Scanlon, Michael J. (Indiana series in the philosophy of religion., 2005)
This volume collects papers and discussion from the third Villanova conference on religion and postmodernism. While studies on and about Augustine as a philosopher abound, few approach his work from a deconstructionist point of view.